Responsibility of the Notary to The Parties in Terms of Binding Purchase Agreement (Ppjb) Based on Their Legal Analysis - Guspitawaty, Elita; Santiago, Faisal (Riviera Publishing, 2023)
A notary is an extension of the government's duty to carry out its responsibilities in the civil field. The presence of a notary is neutral, meaning that it is not affiliated with the government or private agencies, so because of its independence, it does not have to report to the agency but is accountable to the public in this matter to itself. The research method used is normative juridical, where the law is the primary material, jurisprudence, books and journals as secondary material and websites and social media as tertiary material. There are two types of Notary deeds regulated by UUJN, namely actual and authentic. The deed of release is made at the parties' request. It records everything discussed by the parties relating to legal acts or other actions committed by the parties and is outlined in the Notary Deed. While the legal position of Notaries and parties in the sale and purchase binding agreement (PPJB) different, the legal status of Notaries is as a general official who regulates the making of authentic deeds that must be carried out based on the agreement and conditions agreed by the parties. Notaries play a critical role in ensuring that deeds of sale and purchase are legally binding contracts that comply with applicable laws and regulations. Both the seller and buyer must also adhere to the terms of the transaction, while notaries are accountable for their actions and must maintain the highest standards of integrity in fulfilling their duties.